1995
DOI: 10.1136/jnnp.59.3.299
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular tests of autonomic function and sympathetic skin responses in patients with major depression.

Abstract: To assess the function of the autonomic nervous system in major depression, a series of cardiovascular tests, together with the recording of sympathetic skin response, were performed in 18 depressed patients (melancholic type, DSM-III-R criteria) and in 18 healthy control subjects. Depressed patients showed significantly poorer performance in Valsalva's, deep breathing, and lying to standing manoeuvres than controls, indicating an impairment of parasympathetic function. Depressed patients developed a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
1
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(81 citation statements)
references
References 34 publications
3
71
1
6
Order By: Relevance
“…[11][12][13] In this study, significantly lower total power, HF power and HF norm and significantly higher LF norm in both drug naive and medicated depressed patients compared to control suggest lower parasympathetic and higher sympathetic drive and higher LH/HF ratio as index of sympathovagal imbalance in MDD patients. Similar observations were also made by some researchers 8,[16][17] . Several other researchers observed similar trends but it was not statistically significant .…”
Section: Discussionsupporting
confidence: 89%
“…[11][12][13] In this study, significantly lower total power, HF power and HF norm and significantly higher LF norm in both drug naive and medicated depressed patients compared to control suggest lower parasympathetic and higher sympathetic drive and higher LH/HF ratio as index of sympathovagal imbalance in MDD patients. Similar observations were also made by some researchers 8,[16][17] . Several other researchers observed similar trends but it was not statistically significant .…”
Section: Discussionsupporting
confidence: 89%
“…mental health-care practice, reflects the general population of depressed and anxiety patients. Several reports using different SNS indices also found increased sympathetic activity in depressed or anxious subjects (Esler et al, 1982;Gold et al, 2005;Guinjoan et al, 1995;Light et al, 1998;Koschke et al, 2009). These previous reports focused on general sympathetic activity, whereas we measured sympathetic control more narrowly by its effects on cardiac contractility.…”
Section: Discussionmentioning
confidence: 81%
“…These previous reports focused on general sympathetic activity, whereas we measured sympathetic control more narrowly by its effects on cardiac contractility. Guinjoan et al (1995) described a higher sympathetic skin response in 18 melancholically depressed patients compared with 18 healthy controls. Gold et al (2005), reported higher plasma NE levels in 10 subjects with severe melancholic depression than in 12 healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations